On the Destiny of Evil in Leszek Kołakowski’s Thought - BIEGALSKA, AGNIESZKA (Filozofia Chrześcijańska, 2021)
In Leszek Kołakowski’s thought, a devil is not abstract but real. What does he know about it? What do we know? How much of it do we know? It seems that Kołakowski knows it well – he speaks with it, discusses it, and defines it. As if they both were friends. ‘The devil by Kołakowski’ seems to be human-friendly and supportive. Thus, the article poses the following questions: What is the role of evil as defined by Kołakowski in human world and life? How does it work? What is its destiny?